Uji Event Studies: Dampak Peristiwa Aksi Bela Islam (Aksi 212) Terhadap Abnormal Return dan Trading Volume Activity (Saham Syariah di Jakarta Islamic Index) - Nor Hadi; Arum Mediyawati (Universitas Wahid Hasyim Semarang, 2020)
Abstract This article is intended to test the theory of market efficiency hypotheses in weak forms through event studies. Empirical testing in the form of investor response to the massive Muslim demonstration over alleged blasphemy known as action 212. Investors' response testing, in the form of whether the 212 action affects the volatility of abnormal returns and the trading volume of shari'ah stock activity incorporated in Jakarta Islamic Index. The research data are secondary, namely stock returns, stock prices, stock price indexes and sharia stock abnormal returns, with an observation period of 15 days around the date of the action event 212. Data collection by documentation procedures. The number of companies included in the analysis are 26 companies. Data were analyzed using Paired Sample t-Test statistics. The results of testing the hypothesis with empirical data show that the first hypothesis that there are differences in the average abnormal return before and after the 212 action is significantly accepted. Meanwhile, the second hypothesis that there are differences in average trading volume activity before and after the 212 action does not significant (rejected). The results of testing the hypothesis indicate that investors respond to 212 actions in the form of stock price volatility so that abnormal returns are significantly different after and before the 212 action. The response form is also indicated by a wait and see attitude, so that active trading around the 212 action date and after 212 action tends decrease or stagnate.